2021
DOI: 10.1111/ijcp.14300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of erectile dysfunction in patients with asthma

Abstract: Objectives The aim of the current study was to investigate Erectile dysfunction (ED) in asthma patients without comorbidity and the relationship between the level of asthma control and ED. Methods Forty male patients aged 24‐50 years with controlled‐to‐uncontrolled asthma and 20 healthy volunteers were included in this study. The International Index of Erectile Function Questionnaire (IIEF) for ED was used. Results Evaluation of the IIEF scores for ED showed that 23 (57.5%) of the asthma patients and 4 (20.0%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…27 Notably, results herein showed that children in the hearing-loss group were at the highest odds for concurrent asthma. However, this group also had a high variability as seen from the error bars in the Figure . This finding is supported by a report of a randomized clinical trial 29 to examine auditory functions among adults with chronic asthma. The authors reported that hearing loss, especially in high frequencies, presented more often than expected among individuals with concurrent asthma.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…27 Notably, results herein showed that children in the hearing-loss group were at the highest odds for concurrent asthma. However, this group also had a high variability as seen from the error bars in the Figure . This finding is supported by a report of a randomized clinical trial 29 to examine auditory functions among adults with chronic asthma. The authors reported that hearing loss, especially in high frequencies, presented more often than expected among individuals with concurrent asthma.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is supported by a report of a randomized clinical trial to examine auditory functions among adults with chronic asthma. The authors reported that hearing loss, especially in high frequencies, presented more often than expected among individuals with concurrent asthma . The etiology of hearing loss could also include systemic hypoxia associated with asthma.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The potential confounding factors that may affect the association between the TyG index and ED were identified in multivariate adjusted models. Covariates in our study included age (years), race, education level, poverty to income ratio (PIR), marital status (married or living with partner/single), alcohol consumption (drinking or not), cholesterol level (mg/dl), body mass index (BMI), smoking status (yes/no), hypertension, diabetes, asthma ( 27 ), coronary artery disease ( 26 ), testosterone (ng/ml) and estradiol (pg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Başar’s results [27] demonstrated that the controls’ average FSFI score was 27.0 ± 5.1 in contrast to the asthmatic patients’ 22.8 ± 5.6. Kilic and his colleague [32] also reported that the IIEF score of their asthmatic participants was 20.40 ± 6.70, but their counterparts could score 25.55 ± 1.70; furthermore, they discovered that the 19 patients classified as well-controlled can score nearly 5 and 10 points higher in the IIEF score than those regarded as partly and poorly controlled, respectively. Similar findings were also shown in Soto Campos’ article [30], which not only revealed significantly different FSFI (22.14 ± 9.47 vs. 26.57 ± 6.84, p < 0.005) and IIEF scores (59.50 ± 12.57 vs. 64.33 ± 8.28, p < 0.05) among asthmatic and healthy individuals but also disclosed a positive correlation between the level of asthma control and sexual functional score.…”
Section: Resultsmentioning
confidence: 99%